1998
DOI: 10.2355/isijinternational.38.827
|View full text |Cite
|
Sign up to set email alerts
|

Swirling Effect in Immersion Nozzle on Flow and Heat Transport in Billet Continuous Casting Mold.

Abstract: Uniform velocity distribution can be obtained within a very short distance from the outlet of the nozzle.Heat and mass transfer near the meniscus can be remarkably activated comparedwith a conventional straight type immersion nozzle without swirl.Swirl helps the superheat in the melt dissipate,Penetration depth of nozz[e outlet flow is decreased remarkably by the application of swirling.Those findings mentioned above are very useful to control the flow pattern in the biliet and bloom continuous casters,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
80
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 2 publications
3
80
0
Order By: Relevance
“…[35][36][37][38] When using a swirling flow SEN, the penetration depth of the SEN outlet flow in mold was found to decrease. [28] The stability of the steel flow in the mold was enhanced and the defects on the slab surface were effectively reduced. [31] Furthermore, the swirling flow in the SEN was found to effectively reduce the clogging tendency of the SEN port.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…[35][36][37][38] When using a swirling flow SEN, the penetration depth of the SEN outlet flow in mold was found to decrease. [28] The stability of the steel flow in the mold was enhanced and the defects on the slab surface were effectively reduced. [31] Furthermore, the swirling flow in the SEN was found to effectively reduce the clogging tendency of the SEN port.…”
Section: Introductionmentioning
confidence: 95%
“…[36] Therefore, the use of a swirling flow or a rotational flow during metal castings is becoming an important way to produce high-quality steels. However, previous studies [26][27][28][29][30][31][32][33][34][35][36][37][38] of swirling flows during steel castings mainly focused only on the influence on the steel flow itself. Furthermore, previous studies focusing on the inclusion behavior in steel flows have mostly been carried out for conventional continuous casting processes, where no rotational steel flow phenomena exist in the horizontal cross sections of the SEN or the mold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This swirl flow phenomena have extensively been studied by Yokoya and co-workers. [6][7][8][9][10][11][12] Their results have shown that swirl flow helps to control the flow pattern in the mould. Furthermore, that the use of swirl flow in the immersion nozzle enhances the heat and mass transfer in the mould, which in turn helps the superheat in the melt to dissipate.…”
Section: Introductionmentioning
confidence: 97%
“…[6][7][8][9] The flow pattern in the slab-mold has been investigated within a conventional throughput and following results are obtained; The high amplitude of oscillation with a period of 10 to 15 sec observed both at the nozzle-outlet and mold flow are remarkably suppressed imparting a swirling flow in the immersion nozzle, which leads to very calm and stable flow pattern at the outlets of immersion nozzle, in the mold and on the meniscus in the mold. 10,11) Such a effectiveness of swirling flow in the immersion nozzle on the mold flow is also in a trial stage for the practical application.…”
Section: Introductionmentioning
confidence: 99%